Pandangan dan Sikap Imam Ahmad bin Hanbal Terhadap Tokoh-Tokoh Sufi - Faris El Amin, Faris (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2023)
Ahmad bin Hanbal is one of the founders of four schools of jurisprudence which are at the corner of the Madrasah Hadith Expert and is a reference for his followers who call themselves Ahlussunnah. This article examines how Imam Ahmad bin Hanbal interacted with Sufi figures who lived in his time. because of the existence of a shallow paradigm of strong contact between hadith experts and Sufis. This study uses a qualitative descriptive historical approach. The results of this study conclude that there is a good relationship and a careful attitude from Imam Ahmad bin Aanbal towards the practices of the Sufis. and the early Sufis always looked to the Prophet as their ideal model. the description of Ahmad bin Hanbal's interactions with Sufi figures can be called a dialogical interaction between the two. this historically occurred in the second hijri century, especially at the time of Bisyr bin Haristh (227H), Ma'ruf Al-karkhi (200H), Hatim Al-Ashom (237H), Sari As-Saqti (253), Al-Maghazili (282H) ), Zakariya Al-Hawari (255 H).